An experimental and macromechanical study of two-way shape recovery characteristics in NiTi alloy - Wada, Kiyohide (2008)
Thermomechanical treatment can greatly influence the shape recovery characteristics of Nickel Titanium (NiTi) alloy, such as recovery stress, strain and transformation temperatures. One aspect of this treatment is commonly known as “training” where the specimen is thermally cycled under constraint, resulting in the development of stress-assisted two-way memory effect (SATWME). Training is an important process to further develop a spontaneous recovery of hot and cold shapes known as two-way memory effect (TWME). Although extensive experimental and theoretical works have been carried out to date, interpretation of the mechanism giving rise to these memory effects is still unclear and a debatable subject. The present research is dedicated to identify the predominant factors responsible for the development of SATWME and TWME. The characterization of the thermomechanical correlation of these memory effects is of particular interest. The experimental results show that the SATWME and TWME are controlled predominantly by four factors: pre-strain, constrained stress, propagation of martensite deformation during thermal cycling and the nature of thermal cycling (full/partial reverse transformation). Increasing the pre-strain magnitude causes martensite detwinning and dislocation generation. Full utilization of martensite detwinning capacity, whether achieved by the direct application of pre-strain or by the cyclic shift of martensitic strain, results in the maximum SATWME and TWME. The magnitude of constrained stress is critical in determining the microstructural potency to align/realign the generated dislocation structures. Partial reverse transformation through thermal arrest during heating leads to the accommodation of stress-assisted and detwinned martensite variants. Such accommodation process causes the internal forward and back stress formations.